Marketing Tools for Minimizing Risks in the Logistics Strategy of an Enterprise - Ustik, Tetiana; Lagodiienko, Volodymyr; Biloshapka, Yurii; Morokhova, Valentyna; Derenko, Oleksandr (International Review of Management and Marketing, 2025)
The integration of marketing and logistics is a topic of vigorous discourse, underscored by the imperative to establish coherence between supply capabilities and market demand. The purpose of the study is to assess the impact of marketing costs on the company's revenue, while considering the various dimensions of logistics risks, consumer demand, and the development of forecast models for revenue and marketing costs. The study employed correlation and regression methods, alongside comprehensive case analyses. Consequently, the research substantiated the presence of a direct correlation among marketing costs, revenue, demand, and logistics risks. The findings from the regression analysis showed that the income of the examined company is profoundly influenced by marketing costs and logistical risks. Furthermore, marketing costs are in turn impacted by logistical risks and the demand generated by online users. The results obtained can serve as validation of the mitigating effect of employing marketing instruments on the level of logistics risks through the strategic adaptation of marketing costs to the current conditions in global logistics. The findings indicate that such adaptation facilitates revenue enhancement even amidst a logistics crisis and can be leveraged as an effective marketing tool to minimize logistics risks. It should be noted that the developed models are advantageous for enterprises, as they enable the forecasting of revenue and the requisite marketing expenditures based on the anticipated levels of logistics risks and consumer demand. Prospects for further research include the modeling of corporate revenues and costs, incorporating a broader range of indicators (for instance, the logistics cost indicator, contingent upon data availability) and diverse companies. As a result of the present study, a definitive correlation among marketing costs, revenue, consumer demand, and logistical risks was conclusively established.